Comparisons of mean length-based mortality estimators and age-structured models for six southeastern US stocks. (25th October 2019) - Huynh, Quang C; Cummings, Nancie J; Hoenig, John M
Abstract: Length-based mortality estimators have been developed as alternative assessment methods for data-limited stocks. We compared mortality estimates from three methodologically related mean length-based methods to those from an age-structured model (ASM). We estimated fishing mortality and determined overfishing status, i.e. if F / F MSY > 1, for six stocks which support important recreational and commercial fisheries in the southeastern United States. The similarities in historical fishing mortality between the length-based methods and the most recent assessments varied among the case studies, but the classification of overfishing status in the terminal year did not differ based on the choice of model for all six stocks. There was also high agreement in the number of overfishing years within different historical periods. Applications of length-based methods can be consistent with the results that might be obtained from an ASM. In one case, diagnostics were used to identify the problems with the length-based estimators. The potential for determining overfishing status from these methods can encourage data collection programmes for unassessed stocks.